Utilizing the Student Teams Achievement Division (STAD) Model and Counting Boards to Improve Mathematics Learning Results - Aliyyah, Rusi Rusmiati; Talaar, Vania Salsa Nabila (Jurnal Sosial Humaniora, 2025)
The low mathematics learning outcomes of third-grade students at SDIT Annisa in Bogor Regency, which only reached 41.17% in the initial cycle, became the focus of this research. This issue is attributed to the use of traditional teaching methods and a lack of innovative learning media. The aim of this study was to enhance students' mathematics learning outcomes through the implementation of the Student Teams Achievement Division (STAD) cooperative learning model and numbered scoreboard media. This research employed the Classroom Action Research (CAR) model, conducted over two cycles with several stages, including planning, action implementation, observation, and reflection. The subjects of the study were 17 third-grade students, and data were collected through observations, tests, interviews, and documentation. Data analysis techniques utilized both qualitative and quantitative approaches to assess improvements in learning outcomes. The results indicated a significant increase in learning outcomes, where the initial results of 41.17% in the pre-cycle rose to 64.70% in the first cycle and reached 94% in the second cycle. This improvement occurred as student engagement and motivation increased during the interactive and group-based learning process. These findings demonstrate that the STAD model combined with counting board media is effective in enhancing mathematics learning outcomes, as well as encouraging students to be more active and enthusiastic in their learning. This research contributes practically to the development of innovative teaching methods in elementary schools.